2022-VA-1370-ESGO Laparoscopic extraperitoneal systematic para-aortic lymphadenectomy, a step-by-step educational video. (20th October 2022) - Pandraklakis, Anastasios; Liakou, Chrysoula; Burbos, Nikolaos
Abstract : Introduction/Background: Para-aortic lymphadenectomy is part of the standard staging procedure of endometrial cancer. Laparoscopic extraperitoneal para-aortic lymphadenectomy is a feasible alternative technique avoiding the difficulties of the intraperitoneal techniques (extreme trendelenburg, limited surgical space associated problems). Extraperitoneal technique excels due to minimal risks of bowel injury and adhesions formation, avoids trendelenburg position and can be performed in spite of previous abdominal operations. On the other hand, limitations of this technique are the limited surgical space and the lack of anatomical landmarks which can lead to disorientation. The aim of this video is educational, to provide step-by-step the technique of the extraperitoneal para-aortic lymph node dissection. Methodology: We present a case of a 65-year-old woman with serous endometrial cancer stage II grade 3 (FIGO) who operated in our department and underwent laparoscopic extraperitoneal para-aortic lymphadenectomy followed by total laparoscopic hysterectomy (TLH), bilateral saplingo-oophorectomy (BSO) and bilateral pelvic lymphadenectomy. The steps of the extraperitoneal para-aortic lymphadenectomy are listed below:- Intraperitoneal laparoscopy to exclude advanced disease.- Developing the retroperitoneal space- Identification of the anatomical landmarks- Para-aortic lymphadenectomy- Conversion to intraperitoneal laparoscopy for TLH-BSO and pelvic lymphadenectomy Results: Intraoperative and postoperative periods were uneventful. The patient discharged on the next day. Conclusion: Extraperitoneal laparoscopic para-aortic lymphadenectomy is a feasible surgical technique to overcome the conundrums of the intraperitoneal technique even when the patients have history of multiple previous abdominal surgical operations. This technique requires advanced laparoscopic skills and good knowledge of the anatomy of the retroperitoneal space.